Pengaruh Budaya Organisasi, Kompensasi dan Motivasi Terhadap Disiplin Kerja Karyawan Pada PT Inti Palm Sumatra - Meldiana Meldiana; Fajrillah Fajrillah; Ripka Seriindahnaita Ginting (Forum Kerjasama Pendidikan Tinggi, 2021)
This study aims to knows what is the effect of Organizational Culture, Compensation and Motivation of Employee Work Discipline in PT. Inti Palm Sumatra. The method used in this research is descriptive quantitative research methods with the population in this study were 126 people and the sample in this study were 56 people. The analysis technique uses statistical analysis namely classical assumption test, multiple linear regression analysis, hypothesis test, and determination coefficient test. The results showed that partially, it can be seen that organizational culture has an effect on work discipline where the tcount value of 7,900 is greater than the ttable of 2,007 and the significant value of 0,000 is less than 0.05, compensation has an effect on work discipline where the tcount value is more than 2.701. the size of the ttable is 2.007 and a significant value of 0.009 is smaller than 0.05, motivation has no effect on the work discipline where the tcount of 1.057 is smaller than the ttable of 2007 and the significance value of 0.295 is greater than 0.05. Simultaneously, organizational culture, compensation and motivation have an effect on work discipline where the Fcount value of 154.850 is greater than the Ftable of 2.78 and the significant value of 0.000 is less than 0.05. The conclusion states that organizational culture, compensation and motivation simultaneously influence work discipline at PT Inti Palm Sumatra